Cultural Synergy: Participatory Innovation in Maintaining the Sustainability of Muaro Jambi Temple - Asnia, Putriya; Saha, Shagnik; Wijesooriya, Gayan Madhusanka (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This research aims to see how the community participates in efforts to preserve the cultural heritage of Muara Jambi Temple. Methodology: The method used in the research is a qualitative method with a naturalistic qualitative type. The locations in this research are the Jambi Cultural Heritage Conservation Agency as the manager and Muara Jambi Village, Maro Sebo District, Muaro Jambi Regency, Jambi Province. Qualitative methods rely on qualitative data, which can take the form of interviews, participant observation, field notes, or document analysis. Main Findings: The results of this research show that the community already has awareness in preserving the cultural heritage of Muarajambi Temple, which can be proven by the existence of a community founded by the people of Muarajambi Village with awareness of the importance of protecting the environment around Muarajambi Village and the Muarajambi Temple environment. Several forms of community participation, in this case the participation of ideas/thoughts, are considered to be still low because they are not channeled enough. This has not been fully implemented due to a lack of coordination or approach between the community and managers. Various efforts have been made by the management and the community, including protection in the form of restoration, development and utilization of cultural heritage, which can be done through direct promotion or through social media, and Muarajambi Temple is also a scientific, religious, social and cultural institution. Novelty/Originality of this study: The synergy between local culture, participatory innovation and the character of love for one's country is a strong pillar in maintaining the sustainability of Muara Jambi Temple, proving that preserving cultural heritage is a reflection of togetherness and unity in preserving heritage for future generations.